Significance of metacognitive skills in laparoscopic surgery assessed by essential task simulation. Issue 3 (June 2014) - Uemura, Munenori; Tomikawa, Morimasa; Nagao, Yoshihiro; Yamashita, Natsumi; Kumashiro, Ryuichi; Tsutsumi, Norifumi; Ohuchida, Kenoki; Ieiri, Satoshi; Ohdaira, Takeshi; Hashizume, Makoto
Abstract Background: Metacognition is the knowledge about one's own methods of perceiving, remembering, thinking, and acting. This study determined the significance of metacognitive skills in laparoscopic surgery with the aim of applying the findings in a laparoscopic surgery training program. Material and methods: Eighteen medical students with no experience in laparoscopic surgery (novice group) and eight expert surgeons who had each performed >100 laparoscopic surgeries (expert group) were enrolled. The examinees in each group performed an evaluation task using a virtual reality simulator and answered questions about the task. Results: The longest performance times, longest path lengths, and most frequent tissue damage occurred at 135° in the novice group and at 180° in the expert group. The greatest recognition of task difficulties, impatience, and irritation occurred at 135° in the novice group and at 180° in the expert group. There were statistically significant correlation coefficients between the instrument path length and task difficulty (metacognition) at 135° (R = 0.74, p = 0.03) and 180° (R = 0.79, p = 0.02) in the expert group, but there were no significant correlations in the novice group. Conclusion: We elucidated the significance of metacognitive skills in laparoscopic surgery. A training program should include recognition feedback systems.